Perceptions and Performance of Undergraduate Medical Students in Objective Structured Practical Examinations (OSPE) in Biochemistry at Rak Medical and Health Sciences University (Rakmhsu), UAE - Goud, BKM; Begam, S.; Zaki, B.; Haridas, S. (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Health educators and accrediting bodies have defined objectives and competencies that medical students need to acquire to become a safe doctor. The present study was done to determine the student perception and satisfaction regarding OSPE as an assessment method of laboratory practical sessions in Biochemistry. MATERIAL AND METHODS: During OSPE sessions hundred MBBS first year students were divided into 3 different batches. These students were asked to rotate around 10 different working stations. Each station designed to complete a task comfortably within 5 minutes. One or two rest stations of 5 minutes are given at end or in between to complete the unfinished writing work. All the students perform the same task in the same time frame. Institutional research and effectiveness office (IRO) gets the student feedbacks on OSPE will inevitably result in the refinement of the OSPE as a tool for learning and evaluation. RESULTS: The study showed that 96.5% students agreed that OSPE questions were linked to the curriculum and 93% of students felt objectives were clear. Eight eight percent students perceived that OSPE covered a wide range of learning outcomes. Ninety five percent felt relevant psychomotor skills were assessed using agreed check list. An 86% and 81% of student perceived that it was conducted fairly and is unbiased. In terms of stress we got mixed response as 50.5% percent of students perceived OSPE to be less stressful and other half felt stressful. Seventy two percent of students agreed OSPE preparation facilitated team work. Ninety percent strongly agreed that exam scores are better and 83% said it is easier to pass. Fifty four percent of the students felt that the time given was too short; especially for procedure stations. Ninety six percent of students felt OSPE should be an integral part of assessment tool for the Biochemistry practical's. CONCLUSION: The current study showed several advantages of OSPE as an objective, structured, unbiased, fair, valid and reliable assessment method. In view of the tremendous advantages, OSPE should be included in summative evaluation to improve student's clinical competence. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12071 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08 Page: 54-61